An approach to evaluating techniques for vegetation surveys on arid rangelands - Thalen, D.C.P. (International Livestock Centre for Africa, 1981)
Evaluates the usefulness of direct data collection from low-flying light aircraft for inventory & monitoring animal population & other rangeland features, viz. water bodies, vegetation structure & greenness and human settlements, for planning and management purposes.